Perancangan Repositori Arsip Digital Manuskrip Koleksi Museum Sang Nila Utama - Sudiar, Nining; Idayanti, Iik; Latiar, Hadira (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Digital archives of manuscripts or digital manuscripts that are the object of this research are manuscripts from the Sang Nila Utama Museum collection, Pekanbaru. The entire collection has 69 manuscripts, and most of the manuscripts have been restored and italized. Currently, all existing digital manuscripts have not been fully processed and identified. On the other hand, the public is still not able to easily access the manuscripts, because of fears of being damaged and so on. The purpose of this study is to classify the digital manuscripts of the Sang Nila Utama Museum and create a database in the form of a digital manuscript repository for the Sang Nila Utama Museum. This research was conducted at the Sang Nila Utama Museum with a total sample of 70 digital manuscripts. The method used in this research is the observatory method to obtain data in the form of digital manuscripts which will later be used to design information systems and create a digital manuscript repository for the Sang Nila Utama Museum.